Steel construction of modern building of former sports hall at Chopin street in Zielona Góra = Konstrukcja stalowa modernistycznego budynku dawnej hali sportowej przy ul. Chopina w Zielonej Górze - Michalak, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Modernism in architecture of the lubuskie voivodeship is not dominating style. Objects created in the period of its greatest popularity are still fighting for recognition of their value as historical monuments. One of such facilities in Zielona Góra is building at Chopin street, where today is The Teacher Training Centre. However, originally object was intended to be a sports hall.
Keywords: modernizm; konstrukcja stalowa; Beuchelt, Georg (1852-1913); hala sportowa; Zielona Góra; modernism; steel structures; sports hall